Keadilan Gender dalam Hukum Perceraian Islam: Kajian Perbandingan antara Indonesia dan Turki - Endang Zakaria; Usman Alfarisi; Güldane Gündüzöz (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2026)
The pursuit of gender justice within Islamic family law, particularly concerning divorce regulations, remains a pressing legal and social concern in Indonesia. Empirical realities reveal that women often face normative and procedural inequalities in accessing divorce rights. This research undertakes a comparative analysis of the divorce law regimes in Indonesia and Turkiye to assess the degree of legal protection afforded to women undergoing marital dissolution. In the Indonesian context, legal norms continue to privilege the husband's unilateral right to ṭalāq, whereas wives are required to undergo a lengthier and more complex judicial process to dissolve a marriage. Conversely, Turkiye’s secular civil law system is grounded in the principle of formal equality between spouses, ensuring that both parties possess identical legal standing in initiating divorce claims. The judiciary exclusively holds the authority to validate the termination of marriage, and the legal framework provides for spousal maintenance, particularly in favor of the economically vulnerable party. This comparative study underscores the necessity for Indonesia to undertake substantive and procedural reforms aimed at aligning its divorce law more closely with gender-equitable legal standards.